REPRESENTASI FEDERALISME RUSIA PADA UANG KERTAS RUBEL EMISI 1997-2017 - Alfatih, Voja; Elfira, Mina (UI Scholars Hub, 2025)
This study discusses the representation of federalism in the Russian Federation ruble banknotes, issue 1997-2017. The aim of this study is to decipher the images contained in the Russian Federation ruble banknotes, issue 1997-2017, and to explain how far can these images represent federalism in the Russian Federation. The research material used in this study are pictures of ruble banknotes, issue 1997-2017, from the official website of the Central Bank of Russia. The theories used in this study are C.S. Peirce's theory of semiotics, J.D. Peters' theory of money representation, W.H. Riker's theory of federalism, and M. Russel's theory of Russian federalism. The methods used in this research are descriptive method and literary study. The results indicate that federalism can be seen through the use of images such as emblems and landmarks representing the federal government and the federal subject of the the Russian Federation.